(untitled) (Indian Journal of Child Health, 2019)
Background: Acute encephalopathy (AE) outbreak which occurred in Muzaffarpur created an emergency situation with high mortality rate. Objective: This study was conducted to discuss the number of cases presenting with hypoglycemia at the time of admission, the findings of mitochondrial injury, and possible role of environmental factors in the etiology of the disease. Materials and Methods: This is a retrospective study involving 457 patients of AE admitted to Sri Krishna Medical College and Hospital, Muzaffarpur, between March 5, 2019, and July 18, 2019. All the patients who were labeled as known acute encephalitis syndrome (AES) or unknown AES were included in the study. Results: Among 457 cases included in the study group, mean age was 4.88 years. Hypoglycemia was reported in 94.3% of cases. History of litchi consumption was found in 8% and history of skipping meal, the previous night was elicited in 24% of cases. All relevant investigations were carried out in the study subjects. Conclusion: Hypoglycemia is a significant finding in the cases admitted with AES and raised creatine phosphokinase as marker of muscle injury points toward environmental factor as the root cause.